Persistence and Dissipation of Propineb-A Dithiocarbamate Fungicide in Potato under East-Indian Climatic Conditions - Md. Wasim Aktar; M. Paramasivam; Dwaipayan Sengupta (Agriculture and Natural Resources, 2009)
A two season study (Season-I: October, 2005 January, 2006 and Season-II: October, 2006 January, 2007) on the persistence of propineb (Propineb® 70% WP) was undertaken with potatoes at two different locations having two different types of soil: new alluvial and old alluvial, respectively. Two dosage rates were applied: 2.5 and 5.0 kg ai ha-1 twice with a 15-day interval. More than 94% of the initial residues of propineb in the potato tubers dissipated within 15 days after application irrespective of dose, season and location. The residue was detectable up to 20 days after the last application of the fungicide. Assuming first order kinetics, the half-life values varied from 2.59 to 3.48 days. A safe waiting period of 10 days is recommended for potatoes.